Sex differences in morphometry of North Indian acetabula-forensic and orthopedic consideration - Kanika Sachdeva; Rajan Kumar Singla; Gurdeep Kalsey; Preetika Sharma (Wolters Kluwer Medknow Publications, 2019)
Background Acetabulum is a cup-shaped cavity of the hipbone. It constitutes the acetabular part of the hip joint. Its shape and position related to the head of the femur are crucial for the biomechanics of this joint. The knowledge of various acetabular dimensions is essential to diagnose various diseases of hip joint, to monitor patient recovery, to determine stability of the hip joint, to assess acetabular dysplasia, and also to create patient-specific acetabular implants in case of hip arthroplasty. Various parameters of acetabulum differ with respect to age, sex, race, and region. Thus, a region-specific knowledge of the acetabular dimensions will be helpful for surgical reconstruction and sex determination. Materials and Methods The current study was conducted on 100 adult os coxae (male:female = 80:20, right:left = 50:50). The various acetabular dimensions measured were (1) breadth of acetabulum, (2) vertical diameter of acetabulum, (3) maximum depth of acetabulum, (4) linear length of acetabular notch, (5) length of acetabular rim, and (6) total length of acetabular rim with notch. The values were statistically evaluated to find out the sex and side-related differences. Results All the parameters measured were larger in male bones as compared with female bones. Nevertheless, the difference in values was significant only for breadth of acetabulum, vertical diameter of acetabulum, length of acetabular rim, and total length of acetabular rim with notch. Also, the values were more on left side although results were insignificant. Conclusions The results of the present study will provide reference acetabular values for North India region.